An update on head and neck cancer: new entities and their histopathology, molecular background, treatment, and outcome. Issue 5 (27th February 2019) - Andreasen, Simon; Kiss, Katalin; Mikkelsen, Lauge Hjorth; Channir, Hani Ibrahim; Plaschke, Christina Caroline; Melchior, Linea Cecilie; Eriksen, Jesper Grau; Wessel, Irene
Abstract : The head and neck region harbor numerous specialized tissues of all lineages giving rise to a plethora of different malignancies. In recent years, new types and subtypes of cancer has been described here due to the recognition of their histological and molecular characteristics. Some have been formally accepted in the most recent classifications from the World Health Organization (WHO) and American Joint Committee on Cancer (AJCC) as distinct diseases due to characteristics in clinical presentation, outcome, and treatment. In particular, this applies to malignancies of the salivary gland, sinonasal tract, and oropharynx. In this overview, we present the most recent developments in the classification, histopathological characteristics, and molecular features of head and neck cancer. The clinical and radiological characteristics, outcome, and treatment options including perspectives for targeted therapies, are discussed.